2017
DOI: 10.1073/pnas.1615742114
|View full text |Cite
|
Sign up to set email alerts
|

Eight-coordinate fluoride in a silicate double-four-ring

Abstract: Fluoride, nature's smallest anion, is capable of covalently coordinating to eight silicon atoms. The setting is a simple and common motif in zeolite chemistry: the box-shaped silicate double-four-ring (D4R). Fluoride seeks its center. It is the strain of box deformation that keeps fluoride in the middle of the box, and freezes what would be a transition state in its absence. Hypervalent bonding ensues. Fluoride's compactness works to its advantage in stabilizing the cage; chloride, bromide, and iodide do not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 45 publications
(36 reference statements)
3
14
0
1
Order By: Relevance
“…For both SiO 2 -AST and GeO 2 -AST, the energy minimum is located at the center of the cage, and the energy increases smoothly when moving towards a corner. There is a good correspondence between the potential energy curve obtained for SiO 2 -AST and that calculated by Goesten et al for fluoride at the center of a silsesquioxane model of a d4r unit 54. The potential well is somewhat wider for GeO 2 -AST than for SiO 2 -AST due to the larger dimensions of the d4r cage.…”
supporting
confidence: 75%
“…For both SiO 2 -AST and GeO 2 -AST, the energy minimum is located at the center of the cage, and the energy increases smoothly when moving towards a corner. There is a good correspondence between the potential energy curve obtained for SiO 2 -AST and that calculated by Goesten et al for fluoride at the center of a silsesquioxane model of a d4r unit 54. The potential well is somewhat wider for GeO 2 -AST than for SiO 2 -AST due to the larger dimensions of the d4r cage.…”
supporting
confidence: 75%
“…Frequency analysis of the optimized C(CN) 5 − species indeed revealed an imaginary frequency, corresponding to a TS. On a separate, but related quest for hypervalence, Goesten and co‐workers found that fluoride, the smallest existing anion, was capable of coordinating to eight silicon atoms. In this case, the “box” (a key building block of large pore zeolites referred to as double‐four‐ring) had the perfect size to bind F − at its center and set the scene for hypervalent bonding and significant charge transfer.…”
Section: Creation Of Pentavalent Carbonmentioning
confidence: 99%
“…Isoelectronic XeF 7 + and TeF 7 – have been synthesized 16. With the exception of some caged ions,17 higher coordination numbers in neutral main group compounds are, to the best of our knowledge, non-existent. XeF 8 has been shown unstable even under pressures reaching 200 GPa 18.…”
Section: Introductionmentioning
confidence: 97%